2017
DOI: 10.4049/jimmunol.1700560
|View full text |Cite
|
Sign up to set email alerts
|

sIgM–FcμR Interactions Regulate Early B Cell Activation and Plasma Cell Development after Influenza Virus Infection

Abstract: Previous studies with mice lacking secreted IgM (sIgM) due to a deletion of the μs splice region (μs−/−) had shown sIgM involvement in normal B cell development and in support of maximal antigen-specific IgG responses. Because of the changes to B cell development, it remains unclear to which extent and how sIgM directly affects B cell responses. Here we aimed to explore the underlying mechanisms of sIgM-mediated IgG response regulation during influenza virus infection. Generating mice with normally developed μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 51 publications
(58 reference statements)
2
26
0
Order By: Relevance
“…High antigen concentrations make FcmR-mediated stimulation unnecessary ( Figure 5C). A similar observation was described in FcmR flx/flx CD19-cre mice infected with the influenza virus (Nguyen et al, 2017b). In mixed BM chimeras, FcmR-deficient B cells had a significant competitive disadvantage in their ability to differentiate into plasma cells.…”
Section: Discussionsupporting
confidence: 76%
“…High antigen concentrations make FcmR-mediated stimulation unnecessary ( Figure 5C). A similar observation was described in FcmR flx/flx CD19-cre mice infected with the influenza virus (Nguyen et al, 2017b). In mixed BM chimeras, FcmR-deficient B cells had a significant competitive disadvantage in their ability to differentiate into plasma cells.…”
Section: Discussionsupporting
confidence: 76%
“…(5) sIgM can recruit complement components to initiate the classical pathway of complement activation, eventually leading to the formation of the membrane attack complex that can result in lysis of the pathogen. (6) Although the mechanisms are incompletely resolved, sIgM prevents autoimmune antibody formation through multiple mechanisms, including effecting central tolerance induction in the bone marrow and through the removal of DAMPS, such as dead and dying cell debris. (7) The absence of sIgM causes changes in V-gene usage encoding increased self-reactivity tal B cell-depleted mice showed that amount to be more than 90%.…”
Section: Natural Igm Production: Two Sides To a Coinmentioning
confidence: 99%
“…In addition to IgM's direct effector functions and its AIM transport function, studies conducted for over 30 years have shown direct immunoregulatory functions for sIgM. Particularly intriguing are the immune‐enhancing effects of sIgM for inducing maximal IgG responses and the immune‐protective effects against the development of antibody‐mediated autoimmune disease . The mechanisms by which sIgM regulates these processes remain poorly understood, but recent studies have implicated the newly discovered FcµR in facilitating direct interaction of sIgM with cells of the immune system, specifically B and T cells.…”
Section: Introductionmentioning
confidence: 99%
“…B cells shape the early immune response to influenza infection Mice never exposed to influenza virus and even those kept under germ-free conditions nonetheless have circulating "natural" IgM Abs, a fraction of which can bind to a variety of different influenza virus strains (4)(5)(6). This IgM Ab is generated in the bone marrow and spleen of mice by differentiated, neonatally derived subsets of innate-like B cells called B-1 cells (6, 7) and can reduce viral loads and mortality rates from infection (8,9). In addition to this steady-state function, innate-like B-1 cells also respond to influenza virus infection with rapid migration from the pleural cavity to the draining mediastinal lymph nodes (medLN) (5,10).…”
mentioning
confidence: 99%
“…Secreted IgM is a potent facilitator of complement activation (11) and can bind the complement receptors (CR1/2) as well as the Fc receptor for IgM (FcmR) expressed on dendritic cells (DCs), macrophages, and B cells (12,13). Lack of IgM in mice led to delayed influenza clearance (8,9,14,15). IgM-mediated protection from influenza infection is mediated at least in part through activation of complement (15).…”
mentioning
confidence: 99%